Teachers’ Experiences and Instructional Practices in the Implementation of Science 5 Under the Matatag Curriculum in Legislative District IV, Schools Division Of Isabela - Fabian, Jaquilyn; Pascual, Anne Grace (Studies in Technology and Education, 2026)
The implementation of the MATATAG Curriculum in Philippine basic education introduced significant instructional reforms aimed at strengthening foundational competencies, contextualized learning, and learner-centered pedagogical practices. This qualitative study explored the experiences, instructional practices, and implementation challenges encountered by Science 5 teachers under the MATATAG Curriculum in Legislative District IV, Schools Division of Isabela. Utilizing a phenomenological qualitative research design, the study examined how teachers interpret, implement, and adapt Science 5 instruction within the framework of the revised curriculum. Data were gathered through semi-structured interviews, focus group discussions, classroom observations, and document analysis involving twelve purposively selected Science 5 teachers from public elementary schools. Thematic analysis following Braun and Clarke’s framework was employed in analyzing the data. Findings revealed five major themes: (1) Curriculum Adaptation and Instructional Transition Under the MATATAG Framework; (2) Learner-Centered and Inquiry-Based Science Pedagogies; (3) Contextualization and Localization of Science Instruction; (4) Instructional Challenges and Resource Constraints in Curriculum Implementation; and (5) Teacher Resilience, Professional Adjustment, and Pedagogical Innovation. Participants emphasized the importance of simplified competencies, experiential learning, and contextualized science instruction in enhancing learner engagement and conceptual understanding. However, teachers also encountered challenges related to limited instructional materials, insufficient curriculum orientation, time constraints, diverse learner abilities, and adjustment to revised teaching expectations. Despite these challenges, teachers demonstrated adaptability, creativity, and professional commitment in implementing the Science 5 MATATAG Curriculum. The study concludes that successful curriculum implementation requires sustained institutional support, teacher professional development, contextualized instructional resources, and collaborative instructional planning. Findings provide implications for curriculum policy enhancement, science education reform, and teacher support systems in elementary education.